2021
DOI: 10.5604/01.3001.0015.4312
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of low-density polyethylene reinforcement with nano/micro particles of carbon black: a comparative study

Abstract: Purpose: Low density polyethylene is commonly used polymer in the industry because of its unique structure and excellent overall performance. LDPE, is relatively low mechanical properties and thermal stability can sometimes limit its application in industry. Therefore, the development of particulate reinforced polymer composites is one of the highly promising methodologies in the area of next generation engineering products. Design/methodology/approach: Nano and Micro composite from low density polyethylene LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Their results showed that the additions of 2% and 4% CB to LDPE improve the tensile strength of LDPE. However, it was also revealed that the mechanical properties of LDPE improve more by using CB nanoparticles than micro ones 9 . In another study, Marinković et al tried to improve the thermal and dielectric properties of LDPE by doping it with NaA zeolite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that the additions of 2% and 4% CB to LDPE improve the tensile strength of LDPE. However, it was also revealed that the mechanical properties of LDPE improve more by using CB nanoparticles than micro ones 9 . In another study, Marinković et al tried to improve the thermal and dielectric properties of LDPE by doping it with NaA zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was also revealed that the mechanical properties of LDPE improve more by using CB nanoparticles than micro ones. 9 In another study, Marinkovi c et al tried to improve the thermal and dielectric properties of LDPE by doping it with NaA zeolite. In the study, composites containing NaA zeolite additives at rates ranging from 5% to 30% by weight were prepared and it was observed that the thermal conductivity increased as the additive ratio increased.…”
mentioning
confidence: 99%
“…This makes it best for use in applications where moisture is present. LDPE is a plastic waste that contributes to environmental pollution and takes a long time to degrade [7,8]. As illustrated in Figure (1), world plastic production has consistently increased, with a compound annual growth rate of 8.4% since 1950.…”
Section: Introductionmentioning
confidence: 99%